2012
DOI: 10.1038/aja.2012.28
|View full text |Cite
|
Sign up to set email alerts
|

External validation of the Prostate Cancer Prevention Trial and the European Randomized Study of Screening for Prostate Cancer risk calculators in a Chinese cohort

Abstract: Several prediction models have been developed to estimate the outcomes of prostate biopsies. Most of these tools were designed for use with Western populations and have not been validated across different ethnic groups. Therefore, we evaluated the predictive value of the Prostate Cancer Prevention Trial (PCPT) and the European Randomized Study of Screening for Prostate Cancer (ERSPC) risk calculators in a Chinese cohort. Clinicopathological information was obtained from 495 Chinese men who had undergone extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…another study by Zhu et al [19] retrospectively tested the PcPt and erSPc-rcs in a chinese cohort (n = 495). Prostate cancer was diagnosed in 28.7 %, and high grade prostate cancer in 19.4 % of this patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…another study by Zhu et al [19] retrospectively tested the PcPt and erSPc-rcs in a chinese cohort (n = 495). Prostate cancer was diagnosed in 28.7 %, and high grade prostate cancer in 19.4 % of this patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the PTCP-RC involved family history and prior biopsy. Family history [10] and prior biopsy [26] were important indicators in Western countries with higher incidence rate and screening projects. However, the incidence of PCa was quite low in the past few decades in Asian countries, thus there are very few people with family history and previous negative biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…The PCa detection rate of Korean men (19.6%) receiving mainly extended biopsy (75.3% patients underwent extended biopsy) [8] and Chinese men (25.3%) receiving mainly extended biopsy (mean number of cores: 10.4-10.7) [9] was 19.6% and 25.3%, respectively. Urologists in China [10] and Korea [11] found that these 2 RCs would overestimate the risk of PCa by approximately 20% at predicted probabilities from 20% to 80%, indicating the necessity of developing risk prediction models in Asian populations. Secondly, the original ERSPC-RC and PCPT-RC did not include information of prostate volume (PV) or free PSA ratio.…”
Section: Introductionmentioning
confidence: 97%
“…The existing evidence indicates that evaluation of prostate cancer risk should be tailored for different races. [8][9][10] As a result, the development and use of a nomogram for the population from which the nomogram was derived is particularly pertinent. To our knowledge, no nomogram to evaluate the risk of prostate cancer in a Chinese population has been published to date.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that baseline PSA and PSA velocity in young Chinese men without prostate cancer differ from those of African American and Caucasian American men. 9 Furthermore, Zhu et al 10 recently reported that the PCPT and ERSPC risk calculators overestimated the probability of predicting prostate cancer and high-grade disease when independently validated using a Chinese population. The existing evidence indicates that evaluation of prostate cancer risk should be tailored for different races.…”
Section: Introductionmentioning
confidence: 99%